The Effect of Lean Management Implementing in an Efforts to Improve Operational Efficiency in the Emergency Department and Inpatient Units at Royal Prima Hospital, Medan. - Ginting, Dicky Owenta; Girsang , Ermi; Siregar, Santy deasy (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
Hospitals face increasing pressure to provide timely and high-quality care amid rising patient demand, limited resources, and complex service pathways. Inefficient patient flow between emergency and inpatient services often results in prolonged waiting times, suboptimal bed utilization, and reduced patient satisfaction. Lean management has been applied in healthcare to improve operational performance through the elimination of non-value-added activities. This study evaluated the impact of lean management implementation on operational efficiency in the emergency department to inpatient care pathway at Royal Prima Hospital, Medan. A quantitative quasi-experimental study with a pre-test and post-test design was conducted. Lean management interventions were implemented across the emergency department to inpatient admission process, including waste identification, workplace organization, value stream mapping, and continuous improvement activities. Data were obtained from hospital operational records and structured questionnaires administered to healthcare personnel. Operational efficiency indicators included patient waiting time, bed occupancy rate, average length of stay, turnover interval, bed turnover, and patient satisfaction. Data were analyzed using descriptive statistics, paired statistical tests, Pearson correlation, and simple linear regression at a 95 percent confidence level. Lean management implementation significantly improved operational efficiency. Total waiting time from emergency department admission to inpatient transfer decreased from 135 minutes to 74 minutes, representing a 45 percent reduction. Bed occupancy rate increased from 78 percent to 82%, average length of stay decreased from 4.8 days to 4.1 days, turnover interval declined from 1.9 days to 1.3 days, and bed turnover increased from 42 to 48 cycles. Patient satisfaction increased from 72 percent to 86 percent. Pre-test and post-test analysis showed a statistically significant improvement in operational efficiency (p < 0.05). Lean management significantly enhanced patient flow, bed utilization, and patient satisfaction without additional resource investment. These findings support lean management as a sustainable strategy for improving hospital operational efficiency in high-demand clinical settings.